A low-background fluorescent aptasensor for acetamiprid detection based on DNA three-way junction-formed G-quadruplexes and graphene oxide - Zhao, Yunwei; Zhang, Hui; Wang, Ying; Zhao, Yanfang; Li, Yaowei; Han, Lei; Lu, Lihua (Analytical and bioanalytical chemistry, 2021)
A simple fluorescence detection platform has been established for acetamiprid assay based on DNA three-way junctions (TWJs), which can triple the fluorescence signal without any other amplification. It is designed with three single-stranded DNAs (ssDNA), each of which contains one-third or two-thirds of the G-quadruplex sequence at each end. Upon the addition of acetamiprid, the conformation of the aptamer-containing double-stranded DNA (dsDNA) changes from its original conformation and releases a strand of ssDNA. This ssDNA, with the other two ssDNAs, can assemble into DNA TWJs, and the three pairs of the branched ends of the DNA TWJs are adjacent to each other, allowing them to form three units of G-quadruplexes. Hence, the fluorescence of N -methyl mesoporphyrin IX (NMM) is lighted by the nascent G-quadruplexes. Graphene oxide (GO) is then added to minimize the detection background by absorbing the free NMM and non-target-induced ssDNA. The proposed strategy can assay acetamiprid in a wide linear range of 0–500 nM with a detection limit of 5.73 nM. More importantly, this assay platform demonstrates high potential for acetamiprid assay in food control and environmental monitoring.